Distance learning in higher education : a programmatic approach to planning, design, instruction, evaluation, and accreditation - Rovai, Alfred P., ....-; Baker, Jason D., ....-; Ponton, Michael K., ....- (New York : Teachers College, 2008)
1. Concepts of distance learning 2.Gender 3. Culture 4. Strategic planning 5. Program and course design 6. Assessment of student learning 7. Online discussions 8. Program evaluation 9. Institution and program accreditation 10. Course evaluation 11. Summary and conclusion
Keywords: Afstandsonderwijs; E-learning.